Anti-Inflammatory and Anti-Angiogenic Aattributes of Moringa olifera Lam. and its Nanoclay-Based Pectin-Sericin films - Buabeid, Manal Ali; Yaseen, Hafiza Sidra; Asif, Muhammad; Murtaza, Ghulam; Arafa, El-Shaimaa A. (Frontiers in Pharmacology, 2022)
Background: Inflammation is a vital reaction of the non-specific natural immune system that helps to start protective reactions against encroaching pathogens and develop typical immunity against intruding factors. However, prolonged inflammation may lead to chronic autoimmune diseases including osteoarthritis, inflammatory bowel syndrome, gout, diabetes mellitus, rheumatoid arthritis, and cancer. For thousands of years, medicinal plants serve as an excellent source of treatment for chronic pathologies such as metabolic diseases. Purpose: The present study was conducted to evaluate the pharmacological potential of Moringa olifera extract (MO) and Moringa loaded nanoclay films towards inflammation. Moreover, anti-angiogenic potential of MO-loaded nanocomposite films was also investigated. Methods: The preparation of extract was done through the maceration technique in absolute methanol (99.7%) and labeled as Mo.Me. While Mo.Me - loaded nanoclay-based films were prepared by using pectin and sericin. Different in vitro (film thickness, moisture contents, and phytochemical analysis) and in vivo anti-inflammatory (Cotton pellet induced granuloma model) assay were performed. In addition, chick chorioallantoic membrane assay (CAM) was employed for angiogenesis activity. Results: The phytochemical analysis confirmed the presence of alkaloids, glycosides, flavonoids and phytosterol. Cotton-pellet induced granuloma model study revealed comparable (p > 0.05) effect of high dose of Mo.Me (500 mg/kg) as compared with that of standard drug. Noteworthy, data obtained through the RT-PCR technique manifested the dose-dependent anti-oedematous effect of Moringa olifera via downregulation of TNF-α and interleukin-1ß concentration intracellularly. Findings of CAM assay exhibited remarkable anti-angiogenic activity of Mo.Me loaded nanoclay films showing diffused vasculature network in the macroscopic snapshot. Conclusion: These results support the idea that thin film can be applied as an alternative approach to conventional dosage forms. To reiterate, Moringa olifera and its nanocomposite films possess a therapeutic potential against inflammatory disorders; however, clinical trials are suggested.